Association between Vitamin D Deficiency and Risk of Cardiovascular Diseases among Type 2 Diabetes Mellitus Individuals in Bangladesh: a Case Control Comparative Study (Bangladesh Pharmaceutical Journal, 2024)
Type 2 diabetes mellitus (T2DM) is a well-known healthcare problem globally. Several factors, including vitamin D level influence cardiovascular diseases. This study was aimed to determine the association of vitamin D (25 [OH] D) levels and serum lipid profiles with T2DM in Bangladesh. The data (n = 111) were collected from the patients’ register record book of BIHS General Hospital (Mirpur, Dhaka). Clinical (age, gender) and biochemical (fasting glucose level, after meal glucose level, HbA1C, lipid profile (HDL, LDL, TG, cholesterol) and 25-hydroxy vitamin D information were included for analysis. Independent sample t-test (two-tailed) was used to compare diabetic (cases, n  =  70)  and  non-diabetic  (control,  n  =  41) groups.  Correlation  analysis and multiple linear regression assessed unadjusted and adjusted relations between vitamin D levels and other variables, respectively. There was a statistically significant (p